PERAN SEKTOR PARIWISATA TERHADAP PENGENTASAN KEMISKINAN DI PROVINSI JAWA BARAT: ANALISIS DATA PANEL KABUPATEN/KOTA TAHUN 2014–2023 - Revy Rafsanjani Putra Arfandy; Nafisa Zalfa Maulida (STKIP Subang, 2026)
This study examines the role of the tourism sector in poverty reduction across 27 regencies/cities in West Java Province from 2014 to 2023. Using a panel data approach with the Fixed Effect Model (FEM) and VCE Cluster adjustment, the research analyzes the impact of GRDP growth, the number of tourist attractions (ODTW), hotel availability, and tourist arrivals on poverty percentages. Results indicate that, simultaneously, some of these variables significantly influence poverty levels. Partially, the number of tourist attractions is the most dominant factor in significantly reducing poverty, followed by the number of hotels. Conversely, tourist arrivals and GRDP growth show no significant impact. These findings suggest that West Java should shift from mass tourism toward community-based tourism to ensure a more inclusive trickle-down effect for underprivileged communities.